Step-stress model using logistic regression model and its application in medicine - Jamal Ibrahim, Daoud; Khamis, Imad (Pushpa Publishing House, 2010)
A linear logistic model is proposed for estimating the probability of survival to a specified stage using a step-stress model. Parameter estimates may be obtained numerically for the general case of the k-step model, and explicit solutions are given in the case of the two-step stress model. Of special interest to us is the application of this model to the prediction of mortality in HIV-1 infected individuals that based on clinical of Centers for Disease Control and Prevention clinical stage of disease (A, B and C stages). © 2010 Pushpa Publishing House.